2009
DOI: 10.1159/000227787
|View full text |Cite
|
Sign up to set email alerts
|

Intima-Media Thickness of the Carotid Artery and Its Correlation Factors in Maintenance Hemodialysis Patients: A Cross-Sectional Study

Abstract: Background: To investigate the relationship between the intima-media thickness of the carotid artery (CA-IMT) and its major risk factors in maintenance hemodialysis (MHD) patients. Methods: Seventy-five MHD patients and 30 healthy volunteers were enrolled. The MHD patients were divided into 3 subgroups according to their CA-IMT value. Results: CA-IMT values in the MHD group were significantly higher than those in the control group. The differences in age, systolic blood pressure (SBP), and levels of serum albu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Both atherosclerosis and arteriosclerosis are predominant in uremic patients . Atherosclerosis is characterized by plaque formation in medium‐sized arteries while arteriosclerosis is characterized by diffuse calcification and dilation of the medial layer of the aorta and major branches.…”
Section: Cardiovascular Changes In Uremic Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both atherosclerosis and arteriosclerosis are predominant in uremic patients . Atherosclerosis is characterized by plaque formation in medium‐sized arteries while arteriosclerosis is characterized by diffuse calcification and dilation of the medial layer of the aorta and major branches.…”
Section: Cardiovascular Changes In Uremic Patientsmentioning
confidence: 99%
“…Both atherosclerosis and arteriosclerosis are predominant in uremic patients. 18,19 Atherosclerosis is characterized by plaque formation in medium-sized arteries while arteriosclerosis is characterized by diffuse calcification and dilation of the medial layer of the aorta and major branches. In uremic patients, hyperparathyroidism secondary to derangements in calcium, phosphate, fibroblast growth factor 23, and vitamin D homeostasis in CKD patients leads to thickening of blood vessels.…”
Section: Vasculopathymentioning
confidence: 99%
“…However, there has been reported that retinol/RBP4 ratio is strongly and independently associated with CIMT [31]. Transthyretin, which binds with RBP4 and prevents its glomerular filtration and catabolism in the kidney, has been showed to be significantly decreased in patients with CKD [32], and be a significantly independent risk factor of increased CIMT in maintenance hemodialysis patients [33]. Besides, the RBP4 isoforms including apo-RBP4, RBP4-L and RBP4-LL are all elevated in patients with CKD [32].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The association between vascular calcification and cardiovascular events has been well-established in non-CKD populations, and evidence of this association in the CKD population is accruing. A positive association between carotid IMT and coronary artery calcification has been demonstrated in HD patients [25]. …”
Section: Discussionmentioning
confidence: 99%